Technological advancements in improvement of intermodal software and supply chain management of multinational corporations in Uzbekistan - Ergasheva , Shaxrizoda (The Lingua Spectrum, 2025)
The formation and growth of technologies are greatly influenced by supply chains management, which implies that the tourism distribution networks are intimately connected to the world economy. The effectiveness and dependability of supply chain management are essential for multinational firms to succeed in the modern, international economy. With its advantageous location at the intersection of important commercial routes, Uzbekistan is quickly becoming one of Central Asia’s key hubs for logistics and transportation. This study examines the developments in intermodal software technology and how they affect multinational companies’ supply chain management in Uzbekistan.